Perverse politics? : feminism, anti-imperialism, multiplicity - Orloff, Ann Shola; Ray, Raka.; Savci, Evren (Bingley, U.K. : Emerald, 2016)
The papers collected here offer anti-imperialist feminist alternatives to second wave feminism's often reductive understandings of freedom; emancipation; oppression; empowerment and democracy.
In this special issue, we address what we refer to as'perversity of the political' or'perverse politics': namely, the assumptions political theory and movements, and in our specific case feminism, often make on behalf of their subjects, and how their subjects, in return, perform individual and collective contrariness, unruliness and resistance to what is expected or desired from their'subjectivity'. Specifically focusing on the themes of'false consciousness', multiplicity, and uneasy alliances, the papers collected here seek to empirically lay out a number of such'perverse' moments, and offer anti-imperialist feminist alternatives to second wave feminism's often reductive understandings of freedom; emancipation; oppression; empowerment and democracy.
Perverse politics? feminism, anti-imperialism, multiplicity / Ann Shola Orloff, Raka Ray, Evren Savci -- Perverse humanitarianism and the business of rescue: what's wrong with NGOs and what's right about the'Johns'? / Kimberly Kay Hoang -- Redemptive capitalism and sexual investability / Elizabeth Bernstein -- Troubling the subject of violence: the pacifist presumption, martial maternalism, and armed women in contemporary gun culture / Jennifer Carlson -- Feminism/s in power: rethinking gender equality after the second wave / Ann Shola Orloff, Talia Schiff -- Contextualizing the closet: naz, law, and sexuality in postcolonial India / Savina Balasubramanian -- Subjects of rights and subjects of cruelty: the production of an Islamic backlash against homosexuality in Turkey / Evren Savci.
Includes bibliographical references.
Print version record
Keywords: Political Science -- History & Theory; Political science and theory; Feminism -- Political aspects